CEO Turnover and Relative Performance Evaluation - JENTER, DIRK; KANAAN, FADI (Journal of Finance, 2015)
ABSTRACT This paper shows that CEOs are fired after bad firm performance caused by factors beyond their control. Standard economic theory predicts that corporate boards filter out exogenous industry and market shocks from firm performance before deciding on CEO retention. Using a hand‐collected sample of 3,365 CEO turnovers from 1993 to 2009, we document that CEOs are significantly more likely to be dismissed from their jobs after bad industry and, to a lesser extent, after bad market performance. A decline in industry performance from the 90 th to the 10 th percentile doubles the probability of a forced CEO turnover.